2000
DOI: 10.1136/gut.46.6.795
|View full text |Cite
|
Sign up to set email alerts
|

Faecal calprotectin levels in a high risk population for colorectal neoplasia

Abstract: Background-Faecal concentrations of the protein calprotectin have been found to be elevated in patients with colorectal neoplasia, suggesting that it might be used as a screening tool for colorectal cancer as well as adenomas. Aims-To measure the sensitivity and specificity of faecal calprotectin for the detection of adenomas in high risk individuals undergoing colonoscopy. Also, to investigate between and within stool variability of calprotectin concentrations. Subjects-A total of 814 patients planned for col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
54
5

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(67 citation statements)
references
References 18 publications
4
54
5
Order By: Relevance
“…Fish oil with long chain n-3 fatty acids (Paulsen et al, 1998;Bartsch et al, 1999;Stark et al, 2000) 3) Colonic inflammation/faecal calprotectin (Kristinsson et al, 1998;Kronborg et al, 2000) Diets deficient in calcium lead to an exposure of the colon to free bile and fatty acids, and to an inflammatory response (Wargovich et al, 1983;Newmark et al, 1984). The colonic inflammation increases initiation and promotion of colon cancer (Gillen et al, 1994;Biasco et al, 1995;Kristinsson et al, 1999;Okayasu et al, 2002).…”
Section: Study Protocolmentioning
confidence: 99%
“…Fish oil with long chain n-3 fatty acids (Paulsen et al, 1998;Bartsch et al, 1999;Stark et al, 2000) 3) Colonic inflammation/faecal calprotectin (Kristinsson et al, 1998;Kronborg et al, 2000) Diets deficient in calcium lead to an exposure of the colon to free bile and fatty acids, and to an inflammatory response (Wargovich et al, 1983;Newmark et al, 1984). The colonic inflammation increases initiation and promotion of colon cancer (Gillen et al, 1994;Biasco et al, 1995;Kristinsson et al, 1999;Okayasu et al, 2002).…”
Section: Study Protocolmentioning
confidence: 99%
“…As Cal is found in all tissues of the human body, its assessment in several fluids could distinguish between normal and pathological conditions [2]. For instance, an elevated Cal concentration in stools is considered a marker of intestinal neoplasias [6] or inflammatory bowel diseases [7] and helps to distinguish between organic causes of chronic diarrhea and irritable bowel syndrome [8].…”
Section: Introductionmentioning
confidence: 99%
“…In Johne et al (2001) study over 453 symptomatic and asymptomatic CRC cases and healthy controls, a cutoff point of 50 µg/g was calculated with the associated sensitivity and specificity of 89 and 68%, respectively. In another study conducted by Kronborg et al (2000) a cut-off point of 10 µg/g was reported, however, the sensitivity of fecal calprotectin to distinguish CRC from other non-malignancy cases was ranged between 74% and 91% while the specificity was nearly 64%. Finally, Tibble et al (2001) found a sensitivity and specificity of 79% and 72%, respectively, for fecal calprotectin to distinguish CRC or adenomatous polyps from non-malignant lesions.…”
Section: Discussionmentioning
confidence: 99%
“…According to their findings, the median of fecal calprotectin level in the three mentioned groups were respectively 53.4, 30.0, and 4.5 milligram in litre (p<0.05). Similarly, Kronborg et al (2000) surveyed 814 candidates of colonoscopy, among whom, the median of fecal calprotectin level in CRC and normal group were 17.5 and 6.6 milligrams per litre, respectively (p<0.05). Tibble et al (2001) studied in the same area on 62 patients with CRC and 96 individuals as normal group.…”
Section: Discussionmentioning
confidence: 99%